Citrus TISSUE CULTURE WITH TWO DIFFERENT APPROACHES - Chamandoosti, Firoozeh (International Journal of Biosciences and Biotechnology; Vol 8 No 1 (2020): Vol. 8 No. 1, September 2020, 2020)
Citrus is an important genius for economy and human health but a susceptible genius against biotic and abiotic stresses, so it needs to improved programs. Different basal media (MS, ½MA, ?MS and DKW) and different kind and concentrations of plant growth regulators i.e. BA, KIN, 2ip, ZE and TDZ (0 – 2 mg/l) and NAA, IAA and IBA (0 – 2 mg/l) added with 30 g/l sucrose, 3 g/l active charcoal and 7.5 g/l bacteriological agar] were used for organogenesis include shooting and rooting, also callusing from nodal explant of Citrus latifolia. MS medium supplemented with 1 mg/l BA, and 0.01 mg/l NAA is the best media for multiple shoot induction on nodal explants and elongation of them. Other cytokinins had not significant effects on shoot induction and multiplication. Using of 0.01 mg/l IBA instead of 0.01 mg/l NAA on medium with 1 mg/l BA, led to multiple shoot induction on nodal explant indirectly. Rooting was induced on DKW medium plus 1.5 mg/l NAA in the best way compared another media. Both direct and indirect organogenesis (multiple shoot induction) were carried out on media with very similar contents. So we can use very simple and practical methods tissue culture for different improved programs in Citrus genius genius.